Foreword to the Special Issue on "Seafarer's Mental Health and Well-Being" - María Carrera-Arce PhD; Inga Bartusevičienė PhD (SAGE Publishing, 2024)
This special collection encompasses 10 articles that delve into the pressing aspects of seafarers' well-being, mental health, and the workplace. The articles are categorized into 2 broad topics. The first topic, comprising 6 articles, scrutinizes the contributory factors to seafarers' psychological well-being on board, covering sleep problems, food provisions, sexual abstinence, work-life balance, and psychosocial and work environment factors associated with seafaring. Four of these papers also focus on job satisfaction, work effectiveness, and retention in relation to seafarers' psychological well-being. The second topic includes 4 articles on seafarers' mental health assessment and promotion. These articles examine measurement tools for mental health, well-being, and resilience, as well as formal training and technology, including mobile apps, in seafarers' health promotion and education. The insights gleaned from this special collection have the potential to significantly influence the practices of researchers, policymakers, and shipping companies. By shedding light on the need to enhance seafarers' employment characteristics and address the health, safety, and well-being aspects of their work and life, this research can guide these stakeholders to better support seafarers in their crucial role as "key workers."